Acinar Cystic Transformation of the Pancreas: Histomorphology and Molecular Analysis to Unravel its Heterogeneous Nature. (16th March 2023) - Luchini, Claudio; Mattiolo, Paola; Basturk, Olca; Mafficini, Andrea; Ozcan, Kerem; Lawlor, Rita T.; Hong, Seung-Mo; Brosens, Lodewijk A.; Marchegiani, Giovanni; Pea, Antonio; Manfrin, Erminia; Sciacca, Giuseppe; et al.
Abstract : Acinar cystic transformation (ACT) of the pancreas, previously called acinar cell cystadenoma, is a poorly understood and rare entity among pancreatic cystic lesions. This study aims to clarify its real nature. This research cohort included 25 patients with pancreatic ACT, representing the largest series in the literature. We describe their clinicopathological features and molecular profile using next-generation sequencing. ACT arose more often in women (F/M≃2:1), in the body-tail region, with a mean size of ~4 cm. At the latest follow-up, all patients were alive and disease free. Histologically, a typical acinar epithelium lined all cysts, intermingled with ductal-like epithelium in 11/25 (44%) cases. All the cases lacked any evidence of malignancy. Three ACT showed peculiar features: 1 showed an extensive and diffuse microcystic pattern, and the other 2 harbored foci of low-grade pancreatic intraepithelial neoplasia (PanIN) in the ductal-like epithelium. Next-generation sequencing revealed the presence of 2 pathogenic/likely pathogenic mutations in 2 different cases, 1 with ductal-like epithelium and 1 with PanIN, and affecting KRAS (c.34G>C, p.G12R) and SMO (c.1685G>A, p.R562Q) genes, respectively. The other case with PanIN was not available for sequencing. Overall, our findings support that ACT is a benign entity, potentially arising from heterogeneous conditions/background, including: (1) acinar microcysts, (2) malformations, (3) obstructive/inflammatory setting, (4) genetic predisposition, (5) possible neoplastic origin. Although all indications are that ACT is benign, the potential occurrence of driver mutations suggests discussing a potential role of long-term surveillance for these patients.